2015
DOI: 10.1002/pros.23042
|View full text |Cite
|
Sign up to set email alerts
|

PTEN loss and ERG protein expression are infrequent in prostatic ductal adenocarcinomas and concurrent acinar carcinomas

Abstract: Background Prostatic ductal adenocarcinoma is an unusual and aggressive morphologic subtype of prostate cancer. PTEN gene deletion and ERG gene rearrangement are among the most common genomic changes in acinar prostate cancers. Though ductal adenocarcinoma most commonly occurs with synchronous usual-type acinar adenocarcinoma, little is known about the molecular phenotype of these mixed tumors. Methods We used genetically validated immunohistochemistry (IHC) assays to assess PTEN and ERG status in a group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 62 publications
(101 reference statements)
2
26
0
Order By: Relevance
“…In AAC, fusions between the androgen-regulated transmembrane protease serine 2 gene ( TMPRSS2 ) and the ERG estingly, Japanese population gene are present in approximately 40%–50% of cases, where ERG immunohistochemistry correlates well with fusion-positive cancer [24,26]. In the Korean population, the ERG-positive rate by immunohistochemistry was 24.4%, which is lower than those of Western population-based studies [23,27].…”
Section: Discussionmentioning
confidence: 99%
“…In AAC, fusions between the androgen-regulated transmembrane protease serine 2 gene ( TMPRSS2 ) and the ERG estingly, Japanese population gene are present in approximately 40%–50% of cases, where ERG immunohistochemistry correlates well with fusion-positive cancer [24,26]. In the Korean population, the ERG-positive rate by immunohistochemistry was 24.4%, which is lower than those of Western population-based studies [23,27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesised that lower levels of circulating androgens may explain the low s-PSA seen in some DAC and less frequent rearrangements. 58 PTEN loss is less often seen in DAC than in acinar adenocarcinoma. Also, PTEN loss is not enriched in ERG positive DAC, while this is a frequent finding in acinar adenocarcinoma.…”
Section: Molecular Profilementioning
confidence: 93%
“…As PTEN and ERG status are the same in the DAC and acinar components, it is possible that the two tumour types are clonally related. 58 It has been shown that DAC may grow in an environment with low levels of sex hormones, proved by the decreased expression of SQLE, 5AR2 and aromatase. SQLE is the rate limiting enzyme of cholesterol synthesis expressed in prostate cancer cells, especially in prostate cancers of high grade.…”
Section: Molecular Profilementioning
confidence: 99%
“…TMPRSS2-ERG fusion occurs in 11% of the ductal component and in 5% of the acinar component of a mixed tumor, compared with 45%–50% of pure acinar adenocarcinomas [57, 58]. Similarly, PTEN is infrequently lost in the ductal and acinar components of mixed tumors and more often lost in pure acinar adenocarcinoma cells.…”
Section: The 2016 Who Classificationmentioning
confidence: 99%
“…Chromosome 6q15 is frequently deleted in ductal adenocarcinoma cells, and deletions of MAP3K7 , which is harbored in this locus, are associated with early biochemical recurrence, advanced tumor stage, and high GS. MAP3K7 deletions are associated well with the TMPRSS2-ERG absence, which is more common in ductal than acinar adenocarcinomas [58, 63]. …”
Section: The 2016 Who Classificationmentioning
confidence: 99%